Evaluation of PT Semesta Alam Barito's Reclamation Performance as a Commitment to Green Mining Practices - Dedy Waliyan (Prospect Publishing, 2025)
The Government of the Republic of Indonesia has made a mining regulation through Laws, Ministerial Regulations, and Ministerial Decrees that regulate Good Mining Practices, including environmental protection and reclamation. This is also in line with PT Semesta Alam Barito's Quality, Mining Safety, Environment, and Energy Policy, which was made by the Head of Mine Engineering, authorized by the President Director, to be communicated, addressed, complied with, and implemented consistently by all Employees, Work Partners, Visitors, and Suppliers in the mining business license area and project area, it is stated that the Company is committed to protecting and managing the environment with the principle of mitigation and reclaiming disturbed land in every operational activity on an ongoing basis to prevent environmental pollution. The facts show that the Company did not achieve reclamation in 2023. This is a deviation from the Reclamation Plan Annual Work Plan and Budget documents. This research was conducted by the author using quantitative methods through literature studies and direct observation in the field to implement continuous improvement so that the 2024 reclamation plan can be achieved and the lack of reclamation in 2023 can also be achieved at the end of 2024.